Business School Leadership and Crisis Exit Planning Global Deans' Contributions on the Occasion of the 50th Anniversary of the EFMD - Cornuel, Eric (Social Sciences, 2022)
As part of EFMD's fiftieth anniversary celebrations, its President, Professor Eric Cornuel, has edited this volume, featuring contributions from leaders in management education, including the presidents and deans of the top business schools from across the world.